Transmissions des enseignements mathématiques français à l’Académie militaire américaine de West Point (1815-1836) - Thomas Preveraud (Amnis)
In the late 1810s, the officers-engineers’ education at the United States Military Academy, located in West Point, was reformed. The new program was inspired by habits and methods in use in the French schools, and scholar discourses transmitted by French teaching. We show how the contextual processes of knowledge transmission modified the contents taught, principally through textbooks translations. Considering as well the role of American colleges on the Academy productions and their spreading, we support the idea that the French textbooks circulation contributed to an original shaping of American higher education in the 19th century.